The four knowledges of transport planning: Enacting a more communicative, trans-disciplinary policy and decision-making. (August 2017) - Vigar, Geoff
Abstract: There is widespread criticism of much transport planning practice for relying on particular, 'technical', knowledge forms characterized by instrumental, means-end rationality. At the same time politicians are criticized for taking 'political' decisions with not enough regard for the outcomes of such technical work. Increasingly attempts to capture the embodied knowledge and values of citizens are also brought into this contested terrain. But which knowledge forms should be significant in making policy and taking decisions; and how might they be brought together in political decision-making which is itself subject to its own rationality? This paper argues that the variety of knowledge forms in everyday transport planning processes should be more transparently articulated. Subsequent reflexion can help enhance the quality of transport planning processes, while such transparency bolsters the democratic legitimacy of the outputs of such processes. Such a more explicitly communicative, trans-disciplinary mode of governance would help to challenge the power of political rationality. This conclusion has implications for how transport planning as a discipline is enacted. Highlights: An argument for a more communicative approach to transport planning is made. Such an approach should acknowledge the presence of four different types of knowledge in play within any process. This approach has implications for how transport planning as a discipline is enacted and how expertise in the discipline is valued.